WAYS TO IMPROVE STUDENT’S COGNITIVE ACTIVITY IN LEARNING ENGLISH - Otabayev Muzaffar Ne'matullayevich (Scientific Impulse, 2023)
The article deals with the importance of learner's cognitive activity in acquiring the English language and offers numerous strategies to develop the cognition. We know that cognitive learning is a way of learning that helps students use their brains more effectively. This method of learning is active, constructive, and long-lasting. It encourages students to fully engage in the learning process so learning, thinking, and remembering get easier. Cognitive learning isn’t about memorization or repetition. It’s about developing true understanding; it’s about learning how to learn. Thus, this style of learning is a powerful alternative to the traditional classroom approach. Instead of focusing on memorization, cognitive learning builds on past knowledge. Students learn to make connections and reflect on the material—skills that help them become better learners.